Seasonal fluctuations of Rotifera in a tropical lake in Amazonia (Acre River floodplain, Brazil) - Keppeler, Erlei Cassiano; Serra, Alzenira Jacob; Soares Vieira, Lisandro Juno; Pereira, Jardely de Oliveira; Silva, Maralina Torres da; Alencar dos Santos, Maria Jose; Ferraudo, Antonio Sergio [UNESP] (Univ Autonoma Metropolitana-iztapalapa, 2018)
Background: The tropics are centers of high biodiversity of Rotifera that are highly variable and abundant. They play a key role since they are a link in the interaction network with members of other communities. Temporal changes in the community structure of the Rotifera assemblage is related to hydrologic phases. Goals: In this study, we focus on testing the hypothesis that the seasonal changes in alpha diversity and abundance (standing stocks) of Rotifera (Monogononta), considering also limnological variables, are mainly related to rainfall patterns. We consider four seasons based on rainfall: rainy, very rainy, dry, and very dry. Methods: Between 2008 and 2009, rotifers were sampled monthly with a plankton net in qualitative and quantitative sampling, and seven limnological variables were recorded at three sampling stations along Lake Amapa. Results: We found approximately 23% of all Rotifera listed for the Amazonia. The high Menhinick index revealed a high species dominance, except in the rainy season. The Shannon index did riot show a greater distribution of organisms (0.3844 to 0.8886) independent of the layer and time season. In general, the equability index showed that all species were equally abundant in all seasons, with higher values at the surface and in the middle of the water column. The limnological variables also showed differences between all seasons in at least a layer of the water column. Conclusions: The seasons influenced the fluctuations in the communities of Rotifera of Lake Amapa, which led to a different species distribution pattern over time.
Keywords: abundance; oxbow lake; rainfall; zooplankton